Austria : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES Context: Austria did not experience a severe boom-bust cycle and came through the crisis relatively well. The main impact was on the banking sector and public debt. With cyclical slack low and the recovery taking hold, this is the time to resolve crisis legacies and address long-standing structural issues. Outlook and risks: The recovery is taking hold, driven by a pick-up in exports. The most acute risks are mainly geopolitical and could in particular lead to financial spillovers. Financial sector policies: Bank restructuring should now be rapidly completed and bad asset disposal accelerated. Large internationally active banks should stand ready for further capital increases, and the EU banking union framework needs to be swiftly transposed at the national level. Public expenditure reforms: More decisive expenditure reforms in key areas such as pensions, health care, subsidies, and fiscal federalism would generate savings that could be used for both an accelerated debt reduction and lower labor taxation. Boosting potential output growth: Enhancing IT adaptation, improving the performance of the education system, facilitating access to financing for innovative start- ups, and reducing administrative barriers for new businesses would raise potential growth and labor productivity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet